Emotion-oriented systems - Pelachaud, Catherine (London : ISTE, 2012)
'The Affective Computing domain, term coined by Rosalind Picard in 1997, gathers several scientific areas such as computer science, cognitive science, psychology, design and art. The humane-machine interaction systems are no longer solely fast and efficient. They aim to offer to users affective experiences: user's affective state is detected and considered within the interaction; the system displays affective state; it can reason about their implication to achieve a task or resolve a problem. In this book, we have chosen to cover various domains of research in emotion-oriented systems. Our aim is also to highlight the importance to base the computational model on theoretical foundations and on natural data'--
Includes bibliographical references and index.
Keywords: User-centered system design; Human-computer interaction; Interactive computer systems; Virtual computer systems; Emotions and cognition